Heat Risk Interdependencies in the UK: Implications for Adaptation - Sara Mehryar; Candice Howarth; Declan Conway (Earth's Future)
Abstract Heatwaves are becoming more frequent and intense, yet many countries remain inadequately prepared to manage their impacts. Existing heat risk plans and responses often fail to account for the complex interdependencies among the various causes and impact pathways of heatwaves. Effective planning requires a system‐level understanding of these interdependencies to identify strategic entry points for action. This paper employs a participatory system mapping approach to explore the interconnections among causes, impacts, and response actions during the UK heatwave events of summer 2022. Cognitive maps were developed shortly after the events, incorporating input from 38 stakeholders across sectors involved in the heatwave response. These maps informed a forensic disaster analysis designed to provide a holistic understanding of the heatwave's causes, impacts, and adaptation measures. By analyzing the interdependencies among these factors, we identified cascading effects and amplifiers that significantly intensified heat risk in the UK. Notably, we find that the primary heatwave impacts were often indirect, emerging or worsening due to cascading effects such as wildfires, drought, transportation disruptions, and the overburdening of first responders. In many cases, adaptation measures were reactive, addressing isolated, short‐term impacts, while proactive, system‐level approaches tackling interconnected impacts and root causes, such as vulnerable buildings, at‐risk populations, and behavioral barriers, were largely absent. Additionally, we found notable variations in heat risk perceptions among groups. While individual sectors displayed a limited understanding of the broader heat risk system, a system‐level perspective emerged through the aggregation of cognitive maps. The implications for adaptation research and policy are discussed.